INNOVATIVE METHODS IN TEACHING CLINICAL PHARMACOLOGY AT A MEDICAL UNIVERSITY - G. H. Akhmedova; M.I.Mukhitdinova; F.U.Rakhmatova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Relevance. The primary goal of professional education in a medical university is the training of qualified physicians who are capable of effective work in their specialty and competitive in the labor market. High-quality education is strongly associated with the goals of the Bologna Process: academic mobility, diploma recognition, the introduction of credit systems, and innovative technologies in teaching and knowledge management (4). Currently, the main methodological innovations are directly related to the use of interactive teaching methods.